2022
DOI: 10.3390/nu14030581
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects of Drinking Water Produced from Deep Sea Water: A Randomized Double-Blind Controlled Trial

Abstract: Global trends focus on a balanced intake of foods and beverages to maintain health. Drinking water (MIU; hardness = 88) produced from deep sea water (DSW) collected offshore of Muroto, Japan, is considered healthy. We previously reported that the DSW-based drinking water (RDSW; hardness = 1000) improved human gut health. The aim of this randomized double-blind controlled trial was to assess the effects of MIU on human health. Volunteers were assigned to MIU (n = 41) or mineral water (control) groups (n = 41). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…They are freshwater if TDS are less than 1,000ppm, brackish water if TDS less than 1,000-10,000ppm, saline water if TDS less than 10,000-35,000ppm, and hyper-saline water if TDS greater than 35,000. It was reported earlier that deep sea water (DSD)-based drinking water with a hardness level of 1000 enhanced human gut health [7]. Ninety-seven percent of the water in this world is in sea, oceans, and saline groundwater.…”
Section: Drinking Watermentioning
confidence: 99%
“…They are freshwater if TDS are less than 1,000ppm, brackish water if TDS less than 1,000-10,000ppm, saline water if TDS less than 10,000-35,000ppm, and hyper-saline water if TDS greater than 35,000. It was reported earlier that deep sea water (DSD)-based drinking water with a hardness level of 1000 enhanced human gut health [7]. Ninety-seven percent of the water in this world is in sea, oceans, and saline groundwater.…”
Section: Drinking Watermentioning
confidence: 99%
“…In this concern, resistance training (RT) and specific nutritional supplementation (e.g., calcium, vitamin D, creatine, and magnesium) have elicited positive results as non-pharmacological strategies to prevent and treat the abovementioned long-term conditions [ 10 , 11 , 12 , 13 , 14 ]. Previous studies have documented the direct benefits of liquid mineral-enriched supplementation, such as seawater (SW) on human health (e.g., immunological and gastrointestinal) [ 15 , 16 , 17 ] and performance [ 18 , 19 ]. SW has been mostly studied in aerobic-based sports, as it is depicted in a recent systematic review [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…More and more studies have demonstrated that DSW exerts various pharmacological effects, such as the prevention and treatment of hyperlipidemia [ 5 ] and T2DM [ 7 , 8 ], along with improvement of the immune system [ 9 ], anti-tumor properties [ 10 ], and treatment of osteoporosis [ 11 ]. In particular, it has shown promising effects in metabolic diseases [ 5 , 7 , 8 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%